2020
DOI: 10.1177/1473225419893779
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking How We View Gang Members: An Examination into Affective, Behavioral, and Mental Health Predictors of UK Gang-Involved Youth

Abstract: Mental health difficulties, conduct problems, and emotional maladjustment predict a range of negative outcomes, and this may include gang involvement. However, few studies have examined how behavioral, mental health, socio-cognitive, and emotional factors all relate to adolescent gang involvement. This study examined 91 adolescents to compare non-gang with gang-involved youth on their conduct problems, emotional distress, guilt-proneness, anxiety and depression, and use of moral disengagement and rumination. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
0
16
0
2
Order By: Relevance
“…Family members can act as either a risk or protective factor for gang involvement, directly through membership but equally through parenting style and supervision (Aldridge et al , 2012). Gang membership is also associated with negative psychological traits, such as higher levels of mood disorders, rumination (Frisby-Osman and Wood, 2020), lack of impulse control and higher levels of psychopathy (Ashton et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Family members can act as either a risk or protective factor for gang involvement, directly through membership but equally through parenting style and supervision (Aldridge et al , 2012). Gang membership is also associated with negative psychological traits, such as higher levels of mood disorders, rumination (Frisby-Osman and Wood, 2020), lack of impulse control and higher levels of psychopathy (Ashton et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to fear of crime theory (Erčulj, 2021), despite being potentially more vulnerable to knife crime, they did not describe being more fearful; they reported being desensitised towards it. Thus, the interplay of different experiential, environmental, personal and socio-cultural factors may further contribute towards the perceived negative impact of using knife seizure images as a deterrent (Frisby-Osman & Wood, 2020;Leober & Farrington, 2011). The mechanisms by which young people perceive their living environments include primary sources, such as personal experiences with crime, and secondary sources, such as local gossip about antisocial behaviour and crime within the community (Burcar, 2013;Holligan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The NCGR has identified that a holistic understanding of the threat, risk and vulnerability is crucial in informing how criminal justice systems develop gang intervention strategies. The cause-and-effect relationship between behavioral disorders and gang involvement remains disparate, and the social risk factors for gang involvement are multi-faceted (Frisby-Osman and Wood, 2020; Pyle et al , 2020). This study explores how recognizing patterns of offending might aid in identifying particularly challenging mental health profiles in young people whose offending is not limited to within a group or gang.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased prevalence of conduct disorder (CD) among gang-affiliated youth (Livanou et al , 2019; Frisby-Osman and Wood, 2020). CD is recognized as having strong causal links to other psychiatric comorbidities (Fairchild et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation